Advanced Automated Software Testing 2012
DOI: 10.4018/978-1-4666-0089-8.ch006
|View full text |Cite
|
Sign up to set email alerts
|

Test Case Prioritization using Cuckoo Search

Abstract: Test Case prioritization consists of proper organization and scheduling of the test cases in a specific sequence. Regression testing is an important issue and concept during software maintenance process, but due to scarcity of resources re-execution of all test cases, is not possible during regression testing. Hence in version or revision specific regression testing, it is more important to execute those test cases that are beneficial. In this chapter, a new prioritization technique is proposed for version spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Aggrawal et al suggested an approach based on code coverage criteria but this technique especially focuses upon version specific test case prioritization [11]. Srivastava et al proposed a test case prioritization technique on the basis of coverage criteria to increase the value of APFD (Average Percentage of Faults Detected) metric [12]. In 2007 Bryce et al proposed a test case prioritization technique using interaction coverage which was especially presented for Event-driven software [13].…”
Section: Related Workmentioning
confidence: 99%
“…Aggrawal et al suggested an approach based on code coverage criteria but this technique especially focuses upon version specific test case prioritization [11]. Srivastava et al proposed a test case prioritization technique on the basis of coverage criteria to increase the value of APFD (Average Percentage of Faults Detected) metric [12]. In 2007 Bryce et al proposed a test case prioritization technique using interaction coverage which was especially presented for Event-driven software [13].…”
Section: Related Workmentioning
confidence: 99%
“…Later on, many researchers attacked the TCPP. Srivastava proposed a technique that prioritizes test cases based on the fault detection rate calculated from average fault found per minute [29]. Kim and Porter proposed a test prioritization technique based on historical execution data [30].…”
Section: Problemmentioning
confidence: 99%
“…It is therefore important to decide which part of the software should be tested first. For this purpose, test case selection, test suite reduction, and test case prioritization methods are suggested in the literature [26][27][28][29][30][31][32][33][34][35].…”
Section: Related Workmentioning
confidence: 99%
“…Among them, the aim of test case prioritization is to rank the test cases to reveal faults earlier in order to reduce the cost of testing. There are numerous test case prioritization methods proposed in the literature [2,3,4,5,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55].…”
Section: Related Workmentioning
confidence: 99%